2021
DOI: 10.3390/cancers13051154
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 Is Required for Efficient Tumor Initiation and Cancer Stem Cell Maintenance in a Model of Human Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) has a poor outcome compared to other breast cancer subtypes, and new therapies that target the molecular alterations driving tumor progression are needed. Annexin A1 is an abundant multi-functional Ca2+ binding and membrane-associated protein. Reported roles of Annexin A1 in breast cancer progression and metastasis are contradictory. Here, we sought to clarify the functions of Annexin A1 in the development and progression of TNBC. The association of Annexin A1 expression wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 90 publications
(123 reference statements)
1
6
0
Order By: Relevance
“…This investigation corroborates several previous observations, including those which demonstrated ANXA1 expression in the metastatic TNBC cell line MDA-MB-231 was linked to enhanced cell proliferation and cell cycle transition [ 16 ] and that a decrease in cell proliferation was associated with G 1 phase cell cycle arrest following ANXA1 knockdown via siRNA in pancreatic cancer cell lines [ 15 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This investigation corroborates several previous observations, including those which demonstrated ANXA1 expression in the metastatic TNBC cell line MDA-MB-231 was linked to enhanced cell proliferation and cell cycle transition [ 16 ] and that a decrease in cell proliferation was associated with G 1 phase cell cycle arrest following ANXA1 knockdown via siRNA in pancreatic cancer cell lines [ 15 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…To validate the efficacy of MDX-124 in vivo, a syngeneic model of TNBC was chosen. This tumour type is well-documented as expressing high levels of ANXA1 which correlates with poorer survival [ 15 , 34 ]. Furthermore, since a syngeneic model has a fully functioning immune system, both direct and immune-mediated anti-tumour activity caused by ANXA1-targeted therapy can be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this protein has been proposed as a potential EV biomarker for glioblastoma. In a model of human BC, ANXA1 can promote tumor-formation, and it has been suggested that some basal-like TNBCs may require high endogenous tumor cell Annexin A1 expression for continued growth [ 70 ]. In addition, ANXA1 has been suggested to be a useful prognostic marker in HER-2+ BC patients [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 11 genes with risk scores, ANXA1, encoding a membrane‐localized protein, plays an important role in stem cell maintenance and growth 71 . Johnstone et al indicated that ANXA1 was required for cancer initiation and cancer stem cell (CSC) maintenance in breast cancer 72 . Geary et al demonstrated that fibroblast‐secreted ANXA1 induced prostate tumor cells to gain stem‐cell‐like traits 73 .…”
Section: Discussionmentioning
confidence: 99%
“… 71 Johnstone et al indicated that ANXA1 was required for cancer initiation and cancer stem cell (CSC) maintenance in breast cancer. 72 Geary et al demonstrated that fibroblast‐secreted ANXA1 induced prostate tumor cells to gain stem‐cell‐like traits. 73 Insulin‐Like Growth Factor Binding Protein 2, encoded by IGFBP2 gene, is highly expressed in GSCs‐high‐risk gliomas.…”
Section: Discussionmentioning
confidence: 99%